Using the Palembang’s Local Context in PISA-Like Mathematics Problem for Analyze Mathematics Literacy Ability of Students - Nurma Lestari; Ratu Ilma Indra Putri (Universitas Sriwijaya, 2020)
This research is descriptive research that aims to describe how the ability of students' mathematical literacy in solving mathematical problems in the PISA model uses the Palembang context. The research subjects were 10th class in senior high school students. The data collection techniques used are written tests, observations, and interviews. The third technique is used to find out what mathematical abilities that arise when students work on mathematical problems in the PISA model using the Palembang context. There are seven mathematical abilities that emerge, such as 84% communication skills; 88,63% mathematical abilities; 100% representation ability; 68,21% reasoning and argument skills; 86,35% ability to choose strategies to solve problems; 70,45% ability to use symbolic, formal language, and techniques and operations; and 68,17% ability to use mathematics tools so that it can be concluded that the 10th class in senior high school students, who were the subjects of the study had mathematical literacy skills that were good enough.